Niches for Skeletal Stem Cells of Mesenchymal Origin - Kurenkova, Anastasiia D.; Medvedeva, Ekaterina V.; Newton, Phillip T.; Chagin, Andrei S. (Frontiers in Cell and Developmental Biology, 2020)
With very few exceptions, all adult tissues in mammals are maintained and can be renewed by stem cells that self-renew and generate the committed progeny required. These functions are regulated by a specific and in many ways unique microenvironment in stem cell niches. In most cases disruption of an adult stem cell niche leads to depletion of stem cells, followed by impairment of the ability of the tissue in question to maintain its functions. The presence of stem cells, often referred to as mesenchymal stem cells (MSCs) or multipotent bone marrow stromal cells (BMSCs), in the adult skeleton has long been realized. In recent years there has been exceptional progress in identifying and characterizing BMSCs in terms of their capacity to generate specific types of skeletal cells in vivo. Such BMSCs are often referred to as skeletal stem cells (SSCs) or skeletal stem and progenitor cells (SSPCs), with the latter term being used throughout this review. SSPCs have been detected in the bone marrow, periosteum, and growth plate and characterized in vivo on the basis of various genetic markers (i.e., Nestin, Leptin receptor, Gremlin1, Cathepsin-K, etc.). However, the niches in which these cells reside have received less attention. Here, we summarize the current scientific literature on stem cell niches for the SSPCs identified so far and discuss potential factors and environmental cues of importance in these niches in vivo. In this context we focus on (i) articular cartilage, (ii) growth plate cartilage, (iii) periosteum, (iv) the adult endosteal compartment, and (v) the developing endosteal compartment, in that order.